A Stacked Plasmonic Metamaterial with Strong Localized Electric Field Enables Highly Efficient Broadband Light‐Driven CO2 Hydrogenation. Issue 28 (6th June 2022) - Shao, Tianyi; Wang, Xiaonong; Dong, Hanxiao; Liu, Shengkun; Duan, Delong; Li, Yaping; Song, Pin; Jiang, Huijun; Hou, Zhonghuai; Gao, Chao; Xiong, Yujie
Abstract: Light utilization largely governs the performance of CO2 photoconversion, whereas most of the materials that are implemented in such an application are restricted in a narrow spectral absorption range. Plasmonic metamaterials with a designable regular pattern and facile tunability are excellent candidates for maximizing light absorption to generate substantial hot electrons and thermal energy. Herein, a concept of coupling a Au‐based stacked plasmonic metamaterial with single Cu atoms in alloy, as light absorber and catalytic sites, respectively, is reported for gas‐phase light‐driven catalytic CO2 hydrogenation. The metamaterial structure works in a broad spectral range (370–1040 nm) to generate high surface temperature for photothermal catalysis, and also induces strong localized electric field in favor of transfer of hot electrons and reduced energy barrier in CO2 hydrogenation. This work unravels the significant role of a strong localized electric field in photothermal catalysis and demonstrates a scalable fabrication approach to light‐driven catalysts based on plasmonic metamaterials. Abstract : Highly efficient light‐driven catalytic CO2 hydrogenation is achieved by coupling a broadband plasmonic metamaterial absorber with a single Cu atoms based alloy as catalytic sites. The design perfectly synergizes the effects of photothermal conversion, plasmonic hot electrons, and strong localized electric field.